Stability Analysis of Sorensen’s Model for Controllability and Observability: Stability Analysis of Sorensen’s Model - Saleem, Muhammad Umer; Farman, Muhammad; Meraj, M. A. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Stability analysis of a model of glucose insulin glucagon system in humans is made which is one of the important factors for study of model for healthy life. If glucose, insulin or glucagon is negative then it will not be stable and cannot be treated for controllability or observability. Sorenson’s Model is used for this purpose because it is most comprehensive model for glucose, insulin and glucagon in humans. Equilibrium points for different case of concentration of glucose are calculated for stability of the system. Results are refined by using fsolve and fminsearch techniques in Matlab which turn out to be negative value of labile Insulin for all cases and techniques. In this situation we will be unable to find the control of the system in this model